2016
DOI: 10.1021/acs.analchem.6b01037
|View full text |Cite
|
Sign up to set email alerts
|

Typing Pseudomonas aeruginosa Isolates with Ultrahigh Resolution MALDI-FTICR Mass Spectrometry

Abstract: The introduction of standardized matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) platforms in the medical microbiological practice has revolutionized the way microbial species identification is performed on a daily basis. To a large extent, this is due to the ease of operation. Acquired spectra are compared to profiles obtained from cultured colonies present in a reference spectra database. It is fast and reliable, and costs are low compared to previous diagnostic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…recently showed that the ultrahigh resolution and increased dynamic range obtained with a Fourier transform ion cyclotron resonance detector allowed the classification of strains of P . aeruginosa in accordance with cluster analysis based on amplification fragment length polymorphism (AFLP), which was not achieved with a ToF detector 19 . Unfortunately, this technology remains excessively expensive and cumbersome, making it unsuitable for clinical implementation.…”
Section: Introductionmentioning
confidence: 89%
“…recently showed that the ultrahigh resolution and increased dynamic range obtained with a Fourier transform ion cyclotron resonance detector allowed the classification of strains of P . aeruginosa in accordance with cluster analysis based on amplification fragment length polymorphism (AFLP), which was not achieved with a ToF detector 19 . Unfortunately, this technology remains excessively expensive and cumbersome, making it unsuitable for clinical implementation.…”
Section: Introductionmentioning
confidence: 89%
“…Strategies for microorganism characterization by MALDI‐FTICR MS utilize the unsurpassed resolving power (on the order of 100 000 at m/z 1000) and mass accuracy better than 5 ppm . A 15T FTICR system with a MALDI source has been successfully used for discriminating antibiotic resistant and antibiotic susceptible P. aeruginosa strains including isolates from hospital outbreaks . Using ultrahigh mass resolving power mass spectra, the isolates have been clustered in three different groups coinciding with the clustering obtained from amplification fragment length polymorphism data.…”
Section: Current Ms Approaches For Microbial Mixture Analysismentioning
confidence: 94%
“…The complementary metabolomic approach utilized by microbial IMS enabled to visualize metabolic exchange within and among microbial species capturing unique chemical information from fluorescent pseudomonads in particular (Yang et al 2012). Typing of P. aeruginosa clinical isolates using MALDI-FTICR MS allowed the identification of distinct antibiotic resistance patterns in them (Fleurbaaij et al 2016). Inter-kingdom metabolic transformation between P. aeruginosa and Aspergillus fumigatus using MALDI-IMS revealed the characteristic antifungal phenazine compounds secreted by P. aeruginosa were converted by A. fumigatus with altered properties (Moree et al 2012).…”
Section: New Techniques and Tools Helped To Understand Complex Chemicmentioning
confidence: 99%